Analysing the relationship between unemployment rate, inflation rate, and the effect they have on gross domestic product in the United Kingdom (1990-2023) - Lachezar Pavlov; Aleksandar Vasilev (Economics and Econometrics Research Institute (EERI), 2025)
This paper examines the relationship between unemployment rate, inflation rate and economic output in Britain over 34 years. It utilizes a range of different time series techniques, including the ADF and PP unit root test, the autoregressive distributed lag model to cointegration (ARDL model). The modelling provides some useful insights on both the long-run and short-run relationship between the variables. The following results have been produced: The unemployment time series bound test has shown to be inconclusive regarding a long-run relation, while the CPI bounds test showed to have a long-run relation with the other variables, and the bounds test for output showed only a short-run relation. The results in this paper are useful for further development and understanding of the topic and the dynamic interactions on a macroeconomic level.
Keywords: E10; C51; 330; unemployment rate; inflation rate; output; bounds test; ARDL model